AN ANALYSIS OF THE DOMINANCE OF MINANG DIALECT IN KERINCI SOCIETY - Okti Wilymafidini (Politeknik Negeri Bengkalis, 2017)
Abstract: This research aims at explaining the dominance of Minang Dialect in Kerinci Society, the factors that influence the dominance of Minang Dialect in Kerinci society and the way to maintain Kerinci language from the influence of Minang language. This is a descriptive research because it described data and characteristics about the phenomenon being studied. The data was gotten through observation. Besides, the researcher also did library research and compared to the theory used to answer the problems in this research. From the data conducted, it can be seen that the dominance of Minang dialects in Kerinci society can be found in the market and in the restaurants. It means that Kerinci language is influenced by Minang language. This is due to Kerinci and Minang are neighbors. Besides, Minang people who stay in Kerinci always use Minang language especially in doing selling and buying transaction and this gives influence to the use of Kerinci language. Thus, to maintain Kerinci language, there are some steps that can be done such as standardization of Kerinci language, so that people know which one is Kerinci language and which one is not. Besides, Kerinci language dictionary should be available and people have to use the original language of Kerinci instead of Minang language in daily communication.